Defining a problem to fit the solution: A neo-institutional explanation for legitimising the bid for the 2016 Lillehammer winter Youth Olympic Games - Strittmatter, A.-M. (International Journal of Sport Policy and Politics, 2016)
This article discusses the successful bid for the 2016 Lillehammer winter Youth Olympic Games (YOG) and its incorporation within the broader youth sport strategy within organised sport in Norway. Although it is widely accepted that the argument that major sports events are a solution to problems of low levels of involvement in sport is not generally supported by evidence Norwegian sport organisations used this argument as a primary justification for hosting the YOG. The aim of the research is to investigate: a) why NIF used this argument even though there was so little evidence to support its validity; and b) how and why this seemingly contradictory argument was successfully `sold` to the public. The research was guided by the methodological approach of discourse analysis and the theoretical framework of the neo-institutionalist concept of legitimacy. Based on this analysis I show how the institutionalised rhetoric of the Norwegian youth sport policy (YSP) adopted by the Norwegian Olympic Committee and Confederation of Sports (NIF) became the main argument for the YOG bid. Further findings show that rather than responding to the youth sport participation problem, NIF used the development of youth sport as a convenient rationale to bid for the YOG in order to secure legitimacy from two of its main stakeholders - the International Olympic Committee (IOC) and the Norwegian government. Rather than hosting the YOG as solution to a youth sport participation problem, NIF used the institutionalised rhetoric of the YSP, defining a problem to fit the solution.